Implementasi public relation pada usaha laundry di Kota Malang - Sunairah, Sunairah (Maliki Interdisciplinary Journal, 2023)
This research discusses the important role of Public Relations in the success of laundry service businesses, with a focus on the case study of "New Daily Laundry" in the city of Malang. This article outlines the definitions of PR, communication, the laundry business, strategies, and the role of PR in business. The research method involved direct interviews with the owner of New Daily Laundry, using a descriptive approach. The observation results indicate that New Daily Laundry has unique strategies such as a pick-up and delivery system for laundry items and a pricing per package model. They also utilize social media and are responsive to customer reviews. PR strategies in the laundry business include service quality, social media, promotions, customer review responses, customer satisfaction surveys, and employee training. Communication media used include Gmail, apps such as Instagram and WhatsApp, face-to-face interactions, as well as mobile banking for payments. By implementing the right PR strategies, New Daily Laundry can differentiate itself from competitors, build strong customer relationships, and achieve success in the competitive laundry service industry. The research findings are expected to contribute to other business owners and enhance the understanding of the crucial role of PR in the development of the industry. Keywords : Laundry Business, Strategy, Public Relations